Linking Social Entrepreneurship and Social Change: The Mediating Role of Empowerment - Haugh, Helen M. (Journal of business ethics, 2016)
Entrepreneurship is increasingly considered to be integral to development; however, social and cultural norms impact on the extent to which women in developing countries engage with, and accrue the benefits of, entrepreneurial activity. Using data collected from 49 members of a rural social enterprise in North India, we examine the relationships between social entrepreneurship, empowerment and social change. Innovative business processes that facilitated women’s economic activity and at the same time complied with local social and cultural norms that constrain their agency contributed to changing the social order itself. We frame emancipatory social entrepreneurship as processes that (1) empower women and (2) contribute to changing the social order in which women are embedded.